Cancer cachexia: towards integrated therapeutic interventions. (October 2014) - Molfino, Alessio; Formiconi, Alessandra; Rossi Fanelli, Filippo; Muscaritoli, Maurizio
Abstract : Biological treatments represent a novel approach to counteract cancer cachexia. Monoclonal antibodies targeting cytokines and molecules responsible for muscle wasting, with an anti-inflammatory effect, however, still have several limitations and need further clinical investigation. New research in this field will contribute to the better understanding of the multifactorial pathogenesis of cancer cachexia, while favoring the consolidation of multimodal preventive and therapeutic strategies encompassing nutritional and pharmacological treatments. New pharmacological therapies and conventional nutritional treatments will soon integrate in the 'parallel pathway', aimed at early recognition, prevention and treatment of the metabolic and nutritional derangements occurring in cancer. This will likely produce improvement in quality of life, tolerance to treatments and survival.